How important is the final outcome to interpret match analysis data: The influence of scoring a goal, and difference between close and balance games in elite soccer: Comment on Lago-Penas and Gomez-Lopez (2014) - Tessitore, A. (Perceptual and Motor Skills, 2016)
In a recent study, Lago-Penas and Gomez-Lopez (2014) demonstrated that during elite English soccer matches, the percentages of ball possession, entries into the final one-third of the pitch, and shots on goal were lower for the teams with a 1 goal up game status compared to those with 1 goal down condition. In addition, clubs with higher budgets preferred to control the match by dictating the play, primarily through ball possession. Elite soccer coaches may benefit from considering training protocols coherent with the financial budget of their clubs, but these considerations may be valuable also for non-elite soccer clubs. In this comment, studies of various team sports are reviewed, to indicate the need to consider different training drills in relation to competition level, playing positions, and match status of a specific sport discipline. ABSTRACT FROM AUTHOR